Att berätta och återberätta: Intervjuer, narrativ interaktion och berättigande - Cocq, Coppélie (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
This article examines the issue of entitlement in narrative interaction. Based on interviews, it investigates how stories are shaped, transferred and turned from personal to collective stories. Further, the role and the responsibility of the researcher in narrative processes are discussed.